1996
DOI: 10.1046/j.1365-2133.1996.d01-1099.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of interleukins, colony-stimulating factor and tumour necrosis factor on human hair follicle growth in vitro: a possible role for interleukin-1 and tumour necrosis factor-α in alopecia areata

Abstract: The immune system may be involved in the regulation of normal hair follicle growth as well as in the pathogenesis of some hair diseases. Immunomodulatory cytokines not only act as mediators of immunity and inflammation but also regulate cell proliferation and differentiation and, as such, may play an important part in regulating hair growth. We have investigated the effects of a number of interleukins (IL), colony stimulating factors and tumour necrosis factors (TNF) on hair follicle growth in vitro. Dose-resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
141
0
5

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(149 citation statements)
references
References 25 publications
3
141
0
5
Order By: Relevance
“…It is known that the proinflammatory mediators IL-1 and TNF-a are potent MIF polymorphism in extensive alopecia areata T Shimizu et al inhibitors of hair follicle cell proliferation, with a concomitant inhibition of hair growth. 17 MIF is upregulated by TNF-a, and MIF in turn augments the secretion TNF-a. 4,23 Therefore, these inflammatory cytokines may be implicated in the induction or continuation of damage to hair follicles, and MIF may play an important part in the pathophysiology of inflammatory hair loss as in AA.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…It is known that the proinflammatory mediators IL-1 and TNF-a are potent MIF polymorphism in extensive alopecia areata T Shimizu et al inhibitors of hair follicle cell proliferation, with a concomitant inhibition of hair growth. 17 MIF is upregulated by TNF-a, and MIF in turn augments the secretion TNF-a. 4,23 Therefore, these inflammatory cytokines may be implicated in the induction or continuation of damage to hair follicles, and MIF may play an important part in the pathophysiology of inflammatory hair loss as in AA.…”
Section: Discussionmentioning
confidence: 98%
“…16 TNF-a also inhibits hair follicle growth in vitro. 17 The IL-1 and TNF-a gene polymorphisms have been previously investigated. Galbraith et al 18 found evidence of increased susceptibility to AA with certain IL-1/immunogloblin k lightchain genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis is not fully elucidated but studies suggest proinflammatory cytokines such as IL-1α, IL-1β, and TNF-α play a major role in disease progression [14]. As such, one would expect TNF-α inhibitors to be effective treatment options for this condition.…”
Section: Clinical Subtypes Of Alopecia Seen During Treatment With Tnfmentioning
confidence: 99%
“…Various factors may play role in the pathogenesis of AA like cytokines including interleukin I (IL-I) alpha, IL-I beta and tumor necrosis alpha (TNF-α) 119 which is synthesized and released into the extracellular milieu by immune and non immune cells during inflammatory processes leading to stimulation of intracellular production of mitochondrial ROS 120 initiating an increase in the cellular antioxidant defense mechanism, i.e. an increase in SOD and GSH-Px activity 121 .…”
Section: Cholestatic Liver Injurymentioning
confidence: 99%